Mapping surface liquefaction caused by the September 2010 and February 2011 Canterbury earthquakes: a digital dataset. Issue 4 (1st October 2016) - Townsend, D; Lee, JM; Strong, DT; Jongens, R; Smith Lyttle, B; Ashraf, S; Rosser, B; Perrin, N; Lyttle, K; Cubrinovski, M; Taylor, ML; Hughes, MW; et al.
ABSTRACT: We present maps and digital data of the surface manifestation of liquefaction for the two major events during the 2010–2011 Canterbury earthquake sequence, the 2010 Darfield and the 2011 Christchurch earthquakes, in order to show liquefaction extent. Maps include detailed interpretation of aerial photograph mosaics and satellite images captured immediately following each event, and incorporate ground-based surveys of liquefaction occurrences. Evidence of liquefaction includes predominantly silt to fine sand and/or water ejected to the ground surface, and the presence of lateral spreading cracks (with or without ejected sediment). Liquefaction appears to be related to recent alluvial systems, and is more prevalent adjacent to existing waterways and in abandoned stream channels, where young, normally consolidated and poorly compacted sediments are water-saturated. The digital data are available for download in standard geographic information system (GIS) formats, and should provide a reference for future regional scale liquefaction studies.